2022
DOI: 10.1126/sciadv.abo0689
|View full text |Cite
|
Sign up to set email alerts
|

Switch of serotonergic descending inhibition into facilitation by a spinal chloride imbalance in neuropathic pain

Abstract: Descending control from the brain to the spinal cord shapes our pain experience, ranging from powerful analgesia to extreme sensitivity. Increasing evidence from both preclinical and clinical studies points to an imbalance toward descending facilitation as a substrate of pathological pain, but the underlying mechanisms remain unknown. We used an optogenetic approach to manipulate serotonin (5-HT) neurons of the nucleus raphe magnus that project to the dorsal horn of the spinal cord. We found that 5-HT neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…This is in accordance with previous studies in both rats and mice showing increased WDR hyperexcitability in pathological model of persistent pain. 26 , 39 This hyperexcitability was consistent across both male and female mice. By contrast, no changes in the WDR threshold following C-fiber stimulation were observed after SNI in P2X4KO mice or myeloid P2X4KO mice of both sexes, demonstrating the involvement of P2X4 in myeloid cells in dorsal horn neuron hyperexcitability.…”
Section: Discussionmentioning
confidence: 71%
“…This is in accordance with previous studies in both rats and mice showing increased WDR hyperexcitability in pathological model of persistent pain. 26 , 39 This hyperexcitability was consistent across both male and female mice. By contrast, no changes in the WDR threshold following C-fiber stimulation were observed after SNI in P2X4KO mice or myeloid P2X4KO mice of both sexes, demonstrating the involvement of P2X4 in myeloid cells in dorsal horn neuron hyperexcitability.…”
Section: Discussionmentioning
confidence: 71%
“…A recent study revealed that the serotonergic descending pain inhibitory system changes to pain facilitatory properties in neuropathic pain model mice due to a reduction in KCC2 ion transporter (K-Cl cotransporter) expression in the spinal dorsal horn neurons. In this way, serotonergic neuronal transmission is converted from being inhibitory to being excitatory [ 27 ]. However, acute pain due to tissue injury (intraplantar injection of formalin) reportedly stimulates serotonin secretion in the spinal cord more rapidly than does noradrenaline [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the serotonergic descending pain inhibitory system changes to pain facilitatory properties in neuropathic pain model mice due to a reduction in KCC2 ion transporter (K-Cl cotransporter) expression in the spinal dorsal horn neurons. In this way, serotonergic neuronal transmission is converted from being inhibitory to being excitatory [19].…”
Section: Discussionmentioning
confidence: 99%